The enabling environment for disaster risk financing in Fiji country diagnostics assessment. (Metro Manila, Philippines Asian Development Bank, 2019)
This country diagnostic assessment seeks to strengthen financial preparedness for disasters in Fiji, focusing on insurance and other risk transfer instruments.It explores the current application of disaster risk financing solutions by the government, businesses, and individual households; related demand and supply constraints; and opportunities for improvement. The assessment forms one of a series of country diagnostics undertaken using a common methodology to determine the state of the enabling environment for disaster risk financing.
Keywords: Emergency management -- Fiji; Emergency management -- Finance; Electronic books